Urban art in the metaverse: New creative spaces - Bonales Daimiel, Gema; Pradilla Barrero, Nuria (Street Art & Urban Creativity, 2025)
The metaverse emerges as an innovative space for the development of urban art, where virtual reality expands creative, experimental, and interactive possibilities, especially among young people, the most active users in these environments. This study analyzes the perceptions of artists and young citizens regarding digital urban art through a case study, an interview, and three discussion groups. The results reveal that, although Art students are critical of the metaverse, they value it for its ability to foster community participation and digital heritage preservation. Advertising students appreciate its potential to strengthen local identity and pride, while Audiovisual Communication students are more skeptical about the authenticity of digital artistic experiences. In conclusion, this scenario offers an unlimited space for experimentation, interaction, and community participation, though doubts remain about its ability to replicate the physical experience.